Longitudinal DNA methylation changes at MET may alter HGF/c-MET signalling in adolescents at risk for depression. Issue 6 (2nd July 2020) - Ciuculete, Diana M.; Voisin, Sarah; Kular, Lara; Welihinda, Nipuni; Jonsson, Jörgen; Jagodic, Maja; Mwinyi, Jessica; Schiöth, Helgi B.
ABSTRACT: Unrecognized depression during adolescence can result in adult suicidal behaviour. The aim of this study was to identify, replicate and characterize DNA methylation (DNAm) shifts in depression aetiology, using a longitudinal, multi-tissue (blood and brain) and multi-layered (genetics, epigenetics, transcriptomics) approach. We measured genome-wide blood DNAm data at baseline and one-year follow-up, and imputed genetic variants, in 59 healthy adolescents comprising the discovery cohort. Depression and suicidal symptoms were determined using the Development and Well-Being Assessment (DAWBA) depression band, Montgomery-Åsberg Depression Rating Scale-Self (MADRS-S) and SUicide Assessment Scale (SUAS). DNAm levels at follow-up were regressed against depression scores, adjusting for sex, age and the DNAm residuals at baseline. Higher methylation levels of 5% and 13% at cg24627299 within the MET gene were associated with higher depression scores (praw <1e-4) and susceptibility for suicidal symptoms (padj. <0.005). The nearby rs39748 was discovered to be a methylation and expression quantitative trait locus in blood cells. mRNA levels of hepatocyte growth factor ( HGF ) expression, known to strongly interact with MET, were inversely associated with methylation levels at cg24627299, in an independent cohort of 1180 CD14+ samples. In an open-access dataset of brain tissue, lower methylation at cg24627299 was found in 45 adults diagnosed with major depressive disorder compared with matched controls (padj. <0.05). Furthermore, lower MET expression was identified in the hippocampus of depressed individuals compared with controls in a fourth, independent cohort. Our findings reveal methylation changes at MET in the pathology of depression, possibly involved in downregulation of HGF/c-MET signalling the hippocampal region.